NEW COMPLEXES OF INDIUM (111) CONTAINING MIXED LIGANDS (SEMICARBAZONES and BENZALDAZINES). (Sciences & Technology. A, exactes sciences, 2000)
Mixed ligand complexes of indium (111) have been synthesized by the reaction of InCl3.6H2O with semicarbazone (SCH) and benzaldazine (BA) ligands in neutral and basic medium. Complexes of the type [In2 (BA)2 (LH)4]Cl6 and [In2 (BA)2 (L)4]Cl2 (where BA = benzaldazine, LH = semicarbazone ligands (SCH) and L = deprotonated semicarbazone ligands (SC)) have been proposed in neutral and basic medium, respectively. The complexes are characterized physicochemically.